Aseptic Splenic Abscess as Precursory Extraintestinal Manifestation of Inflammatory Bowel Disease - Joel Brooks; Gisoo Ghaffari (Case Reports in Medicine)
Splenic abscesses are most often secondary to aerobic bacterial infections due to Streptococcus, Staphylococcus, and Enterococcus species of organisms. Sterile splenic abscesses rarely occur and diagnosis and treatment of those are challenging. We report a case of a previously healthy young female presenting with aseptic splenic abscesses as the initial manifestation of Crohn’s disease along with a review of the literature on aseptic splenic abscess as an extraintestinal manifestation of Crohn’s disease.